Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1161/atvbaha.117.309473
|View full text |Cite
|
Sign up to set email alerts
|

Inner Mitochondrial Membrane Disruption Links Apoptotic and Agonist-Initiated Phosphatidylserine Externalization in Platelets

Abstract: Objectives Phosphatidylserine (PSer) exposure mediates platelet procoagulant function and regulates platelet lifespan. Apoptotic, necrotic, and integrin-mediated mechanisms have been implicated as intracellular determinants of platelet PSer exposure. Here we investigate 1) the role of mitochondrial events in platelet PSer exposure initiated by these distinct stimuli and 2) the cellular interactions of the procoagulant platelet in vitro and in vivo. Approach and results Key mitochondrial events were examined,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…Heterogeneity within the PS-exposing platelet subpopulation has also been reported by Topalov et al (80): one subset with high Ca 2+ cyt , m loss, and inactive αIIbβ3; and another with low Ca 2+ cyt , intact m , and active αIIbβ3. Subsequently, this latter subset was described to be the result of the interaction between a procoagulant platelet and an aggregatory (non-PS-exposing) platelet (81).…”
Section: Agonist-induced Phosphatidylserine Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneity within the PS-exposing platelet subpopulation has also been reported by Topalov et al (80): one subset with high Ca 2+ cyt , m loss, and inactive αIIbβ3; and another with low Ca 2+ cyt , intact m , and active αIIbβ3. Subsequently, this latter subset was described to be the result of the interaction between a procoagulant platelet and an aggregatory (non-PS-exposing) platelet (81).…”
Section: Agonist-induced Phosphatidylserine Exposurementioning
confidence: 99%
“…It is also caspase dependent, as responses are abolished in the presence of a caspase inhibitor (52,78). However, it does not require increases in Ca 2+ cyt or calpain activity, which are necessary for agonist-induced PS exposure (52) (Agonist-Induced Phosphatidylserine Exposure) There is early mitochondrial outer membrane permeabilization (MOMP), followed by later IMM disruption concomitant with PS exposure (81): MPTP formation may not be involved, and m depolarization may occur (52,(103)(104)(105). PS-exposing platelets take on a rounded morphology but maintain cytoplasmic components (105,106); EV formation is not observed early on, but increases with time (103,104,107).…”
Section: Apoptosis-induced Phosphatidylserine Exposurementioning
confidence: 99%
“…To investigate the effect of these putative BH3 mimetics on mitochondrial membrane potential, platelets were loaded with TMRM. This reflects late damage to the mitochondria rather than early release of cytochrome c [4,18]. The timecourse of loss of TMRM fluorescence matched that AnV binding.…”
Section: Comparison Of the Effects Of Putative Bh3 Mimetics On Ps Expmentioning
confidence: 65%
“…As noted, mitochondrial depolarization is essential for procoagulant platelet synthesis, although the details of how this occurs are poorly understood. Choo et al 15 have cleverly examined several mitochondrial changes and observed that disruption of the inner mitochondrial membrane, with either proapoptotic agents or dual agonist stimulation, is critical to the process of PS exposure. However, disruption of the outer mitochondrial membrane and release of cytochrome C, as observed in apoptosis, does not occur in procoagulant platelet formation.…”
Section: See Accompanying Article From the August 2017 Issue On Page mentioning
confidence: 99%
“…The second observation by Choo et al 15 concerned a report that challenged the pentad of characteristics for procoagulant platelets. Topalov et al 16 observed that high levels of thrombin stimulation produced PS-positive platelets that retained polarized mitochondria and functional GP (glycoprotein) IIb/ IIIa receptors, labeling their new class of platelets as integrinregulated procoagulant platelets.…”
Section: See Accompanying Article From the August 2017 Issue On Page mentioning
confidence: 99%